Organizing for expropriation: How a tenants campaign convinced Berliners to vote for expropriating big landlords - Lisa Vollmer; Daniel Gutiérrez (Radical Housing Journal, 2022)
On 26 September 2021, 59% of Berliners eligible to vote decided in a referendum for the expropriation of big landlords and to socialize approximately 250.000 housing units. This article looks at how the campaign Expropriate Deutsche Wohnen & Co was able to do so. The article begins by introducing conceptualizations of social movement impacts. It then expands on these conceptualizations with a thick description of the emergence and the organizational structure of the expropriation campaign, including the material basis of the campaign, the dire situation of Berlin’s tenants, the organizational ecology of the tenant movement out of which the campaign grew, the political terrain and public discourse the campaign had to navigate, and at the organizational process of the campaign itself. Drawing on such thick description, we revisit and add nuance to the conceptualizations of social movement impact in social movement studies, and highlight the complex interplay between different factors and their effect on different stages of the political process.